Thaumatographia oder Zur Kritik der philologischen Vernunft: Vorspiel: Die Jagd des Aktaion (Ovid, Metamorphosen 3,131-259) - Schwindt, Jürgen Paul (Bibliothek der klassischen Altertumswissenschaften / 2, 2016)
Volume 150 in the series introduces a new perspective on philology. It is developed through an analysis of one of the basic texts of European literature. Ovid's version of the myth of Actaeon in the "Metamorphoses" revolves around the border between inside and outside, God and man, man and animal, animal and prey, nature and culture, master and slave. This is more than a drama of seeing, it is a drama of language and control over language. Understanding the catastrophe at the heart of civilization, "experimentum crucis," stands at the center of the poetics of the "Metamorphoses." And philology? Philology as the archaeology of the modern observes how the text thinks all the synchronicities and inconsistencies, the atopias and utopias, the paradoxes and the paroxysms of art and life and also of thought, and is amazed when it recognizes itself in the interpretation, in this "protocol of oddities or wonders" (thaumatographia)